Genetic relationship between reproductive traits in Nellore cattle - Guarini, Aline Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to estimate genetic parameters between scrotal circumference obtained at 18 months of age (SC) and reproductive traits measured directly in Nellore females, such as number of calvings at 53 months (NC53), heifers rebreeding (HR) and stayability (STAY) in order to investigate the possibility of using traits measured directly in females as a selection criteria in cattle breeding programs, besides, studying and evaluating if number of calvings at 53 months could be used as an alternative way for measuring longevity in cattle herds. Two methods were applied for estimating variance components in order to predict breeding values: restricted maximum likelihood (REML) and Bayesian inference. The average estimates of heritability by bivariate model using REML were equal to 0.013 ± 0.003, 0.057 ± 0.007, 0.039 ± 0.007 and 0.530 ± 0.013 for NC53, STAY, HR and SC, respectively. Using the Bayesian method, the estimates were 0.22 ± 0.009, 0.19 ± 0.025, 0.15 ± 0.021 and 0.52 ± 0.019 for NC53, STAY, HR and SC, respectively. Based on the correlations between reproductive traits measured in females, the selection of animals for NC53 will cause anticipation on genetic evaluation of bulls for longevity, based on the performance of their daughters, from 76 to 53 months
Keywords: Bovino de corte - Reprodução; Bovino de corte - Melhoramento genetico; Nelore (Zebu); Genetica animal; Teoria bayesiana de decisão estatistica; Animal genetics